Answer:
2·(a^2 + b^2) = (a + b)^2
2·a^2 + 2·b^2 = a^2 + 2·a·b + b^2
a^2 + b^2 = 2·a·b
a^2 - 2·a·b + b^2 = 0
(a - b)^2 = 0
a = b
Answer:
1/6
Step-by-step explanation:
Yea don’t click on the links the get information from u
Answer:
Pyramid Distribution
Step-by-step explanation:
I don't know the answers but from what I know it has to be pyramid distribution or triangle distribution Hope This Helps!
Answer:
ok i dnt know but
Step-by-step explanation:
go to https://mathsolver.microsoft.com/en/solve-problem/2%20%60left(%20y-3%20%60cdot%20%204%20%20%60right) if it dnt work try a calculator